Effectiveness Of Village Fund Management On Increasing Community Welfare With Management Religiosity Behavior As Moderating Variables - Aswadi Lubis (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
Community welfare is one of the goals expected by each region including in Padangsidimpuan city. Based on data obtained the amount of poverty in Padangsidimpuan city experienced fluctuations from 2008 to 2015. The formulation of the problem in this study is whether there is an effect of the effectiveness of village fund management on improving the welfare of rural communities in Padangsidimpuan city. Does the manager’s religiosity behavior moderate the influence of village fund management by increasing the welfare of rural communities in Padangsidimpuan City? This type of research is causality research using quantitative data. The population of this study is the village community in the city of Padangsidimpuan with a total of 41 villages. Given the limitations of the author, the sample in this study was taken by 5 people from each village, namely 5 x 41 villages = 205 villagers. Data collection techniques used were questionnaires and data analysis conducted with Smart PLS. Based on the results, it was found the value of the village fund management pathway affected the welfare of the village community of 5.875 with a probability value of 0.024. Because the t-count value (5.875) is greater than critical t (1.96) at the 5% error rate, it can be concluded there is an effect of the effectiveness of village fund management on improving the welfare of rural communities in Padangsidimpuan City. And the t-count value of the manager's religiosity behavior trends moderates the relationship of village fund management to rural community welfare of 0.458 with a probability value of 0.031. Because the t-count (0.458) is greater than the critical t (1.96) at the 5% error rate, it can be concluded that the manager's religiosity behavior can moderate the relationship between village fund management and the improvement of the welfare of rural communities in Padangsidimpuan City.